2003
DOI: 10.1016/s1059131102001504
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s perspective on epilepsy: self-knowledge among Omanis

Abstract: Improving patients' knowledge has been suggested to improve their symptoms and prognosis. Very little is known about epileptic patient's knowledge of their illness in cross-cultural settings. This pilot study investigated what Omani patients know about their disorder. Patients attending a tertiary hospital completed a structured knowledge questionnaire to elicit information pertaining to aetiology, safety, compliance with medication regimes, legal and employment issues concerning epilepsy.Although correctly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The correct-answer rate was low for the danger of taking a shower or bath alone, which may be attributable to PWE focusing on the risk of falling down. The low correct-answer rate for the continuous wearing of identification bands is in accordance with previous studies 1,17,27. Despite the obvious benefits of wearing a band, social prejudices in Korea may make this difficult for PWE.…”
Section: Discussionsupporting
confidence: 90%
“…The correct-answer rate was low for the danger of taking a shower or bath alone, which may be attributable to PWE focusing on the risk of falling down. The low correct-answer rate for the continuous wearing of identification bands is in accordance with previous studies 1,17,27. Despite the obvious benefits of wearing a band, social prejudices in Korea may make this difficult for PWE.…”
Section: Discussionsupporting
confidence: 90%
“…There is a need for psychological and counselling services to address the issues related to an early onset of epilepsy. Moreover, efforts should be made to include educating people with epilepsy and their families to address the relation between knowledge, stigma and adjustment, 28,29 as well as targeting the general public and the various organisations with which people with epilepsy connect. 30…”
Section: Discussionmentioning
confidence: 99%
“…A study c arried out by the Department of Neurology at St. James Hospital and the School of Medicine, Trinity College, concluded that many people with epilepsy are not properly informed about their disorder [4]. People with epilepsy often present with attitudes that are potential breeding ground for myths, stigma and exclusion [5,6]. Without adequate knowledge, people with epilepsy are likely to become the victims of other people's negative beliefs and misconceptions.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this, people with epilepsy may be less likely to come to terms with their condition. Studies carried out in developing countries have examined cultural attitudes and awareness of epilepsy [6,10]. However, there is still a need for more investigations to be conducted to evaluate the knowledge of people with epilepsy about their condition.…”
Section: Introductionmentioning
confidence: 99%